2018
DOI: 10.1038/s41598-018-34014-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary emphysema on exercise capacity and its physiological determinants in chronic obstructive pulmonary disease

Abstract: Exercise limitation is common in chronic obstructive pulmonary disease (COPD). We determined the impact of pulmonary emphysema on the physiological response to exercise independent of contemporary measures of COPD severity. Smokers 40–79 years old with COPD underwent computed tomography, pulmonary function tesing, and symptom-limited incremental exercise testing. COPD severity was quantified according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) by spirometry (GOLD 1–4); and symptom bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Minimizing exposure to both smoking and indoor air pollution decreases the rate of disease progression and is positively correlated with a decrease in mortality [67,68]. Physical activity is exceptionally important in reducing exacerbation frequency and mortality rates in patients with COPD [69][70][71][72]. Other interventions include vaccinations against influenza and pneumococcal infections, as these may reduce the risk of exacerbation events and hospital admission [73,74].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Minimizing exposure to both smoking and indoor air pollution decreases the rate of disease progression and is positively correlated with a decrease in mortality [67,68]. Physical activity is exceptionally important in reducing exacerbation frequency and mortality rates in patients with COPD [69][70][71][72]. Other interventions include vaccinations against influenza and pneumococcal infections, as these may reduce the risk of exacerbation events and hospital admission [73,74].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Several studies have shown that an increased V D /V Tphys , partially due to emphysema [21,23,25,28,96,97], constitutes an important correlate of a high V′ E /V′ CO 2 . As discussed later, this is particularly true in patients who are not severely compromised from the mechanical standpoint, i.e.…”
Section: Structural and Functional Determinants Of V′ E /V′ Co 2 In Copdmentioning
confidence: 99%
“…3 Emphysema is a major determinant to predict lung function decline and mortality in COPD patients independent of airflow limitation. 6 Also, CTquantified emphysema in COPD patients is associated with exercise intolerance, impaired gas-exchange independent of airflow limitation, symptom scale and exacerbation risk was shown by Smith et al 7 Computed tomography (CT) is a well-validated technique to visually and quantitatively assess the presence, pattern and extent of emphysema, and a standardised characterisation of COPD on CT is crucial. 8 Determining COPD phenotypes related to emphysema severity can be important in properly managing the treatment and subtyping of the disease, and emphysema severity can be used as a predictor of COPD and functional impairment of the patients.…”
Section: Introductionmentioning
confidence: 99%